The Routledge handbook of African law - Ndulo, Muna; Emeziem, Cosmas (Routledge, 2022)
"The Routledge Handbook of African Law provides a comprehensive, critical overview of the contemporary legal terrain in Africa. The international team of expert contributors adopt an analytical and comparative approach so that readers can see the nexus between different jurisdictions and different legal traditions across the continent. The volume is divided into five parts covering: Legal Pluralism and African Legal Systems, the State, Institutions, Constitutionalism, and Democratic Governance, Economic Development, Technology, Trade and Investment, Human Rights, Gender-Based Violence, and Access to Justice International Law, Institutions, and International Criminal Law Providing important insights into both the specific contexts of African legal systems and the ways in which these legal traditions intersect with the wider world, this handbook will be an essential resource for academics, researchers, lawyers, graduate and undergraduate students studying this ever-evolving field"--
Keywords: Recht; Justiz; Afrika; Law / Africa; Law; Africa; Aufsatzsammlung